2021
DOI: 10.3390/polym13101561
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose Nanocrystals as Template for Improving the Crystallinity of Two-Dimensional Covalent Organic Framework Films

Abstract: Despite the rapid development of two-dimensional covalent organic frameworks (2D COFs) in recent years, it remains a great challenge to synthesize highly crystalline COF materials. Here, a CNC-assisted approach was adopted to synthesize high crystallinity COF materials. A series of 2D COF films were synthesized at the air–water interface by using cellulose nanocrystals (CNCs) as the template. The occurrence of Schiff reactions based on the imine bond was demonstrated by Raman spectroscopy and Fourier transform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 45 publications
(45 reference statements)
2
6
0
Order By: Relevance
“…The N 1s spectra of AuNPs@2-MBQ@COFs were divided into 398.55 and 399.40 eV corresponding to CN and −NH 2 , respectively . And there were two peaks at 531.40 and 532.45 eV in O 1s spectra, which belonged to the CO group and air contamination . The XPS spectra of S 2p and Au 4f indicated that the 2-MBQ was modified on the surface of AuNPs according to the Au–S bond .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The N 1s spectra of AuNPs@2-MBQ@COFs were divided into 398.55 and 399.40 eV corresponding to CN and −NH 2 , respectively . And there were two peaks at 531.40 and 532.45 eV in O 1s spectra, which belonged to the CO group and air contamination . The XPS spectra of S 2p and Au 4f indicated that the 2-MBQ was modified on the surface of AuNPs according to the Au–S bond .…”
Section: Resultsmentioning
confidence: 98%
“…51 And there were two peaks at 531.40 and 532.45 eV in O 1s spectra, which belonged to the C�O group and air contamination. 52 The XPS spectra of S 2p and Au 4f indicated that the 2-MBQ was modified on the surface of AuNPs according to the Au−S bond. 53 From the SERS spectra of AuNPs@2-MBQ@COFs and AuNPs@2-MBQ shown in Figure 2D, the bands located at 840 cm −1 (stretching vibration of C�O and CCC) and 985 cm −1 (stretching vibration of C�O and bending vibration of CCC) belonged to the characteristic peak of 2-MBQ molecules.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…As seen in the gure, the thin-lm shows the characteristic absorbance peaks are observed at 470 nm [Soret (S) band] and 575 nm [Q band]. 58 The slight redshi of the absorption edges observed may be due to the presence of QD's in the COF thinlm. To further understand the structural information of the COF366-QDs lm, it was examined by high-resolution X-ray photoelectron spectra (XPS).…”
Section: Resultsmentioning
confidence: 94%
“…Another peak with higher binding energy and a minor peak at around 397.7 eV and 400.3 eV was observed representing non-protonated nitrogen structure and Ph-NH 2 of porphyrin in 3b). 55,58 The surface topology analysis of the thin-lm (S3) was studied by atomic force microscopy as shown in Fig. 4a-c and the average thickness of the COF366-QD thin lm was found to be ∼112 nm (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation